Judicialização da saúde: análise sobre o controle judicial nas hipóteses de medicamentos e tratamentos não previstos nas políticas públicas de saúde - Corrêa, Gina Fonseca (2022)
Objective. Analysis of judicial control over drugs and treatments not provided for in public health policies. Examination of the limits of the Judiciary's action in the face of the principle of separation of powers and the duty to promote fundamental rights. Justification. Research carried out in 2019 shows that, despite a certain improvement in data on public health care, it is still insufficient for the realization of the right to health in constitutional and conventional terms. Access to medicines and treatments is deficient. While a significant part of the judicial demands is about what fits in public policy, this work is interested in the demands about what was not incorporated, seeking to understand the role of the Judiciary in the lawsuit, since the volume of services and costs that involve the theme. Hypothesis. The legitimacy of the Judiciary's action in the control of public policies, especially regarding medicines and treatments not included in health protocols, such as CONITEC, NAT, RENAME, RENASES, REMUNE. Methodology. The research will follow a systemic and dogmatic approach, investigating concepts and categories to understand the unity of the legal system, especially the effects and consequences. Results obtained. The Judiciary has a constitutional duty to implement the fundamental right to health, respecting the empirical data and technical assessments of the Public Administration. A judicial decision not based on empirical evidence may imply an invasion of the other Powers. In the event of illegitimate omission by the Public Administration or the Legislature, judicial control will be exercised through an examination of proportionality, giving greater weight to the criteria that favor the universalization of health actions and services